PENINGKATAN KECEPATAN PROSES PADA METODE COLOR ORDERING DAN MAPPING DENGAN PENDEKATAN DELAPAN-KETETANGGAAN - Astried Astried; Tri Basuki Kurniawan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2009)
The development of digital technology and internet, nowadays, has given the facility for easy access and distribution of a lot of information in digital form. The facilities in distributing digital data also has emerged the negative impact such as the violence of copy right. One of techniques developed from negative impact is water making technique. Several techniques have been mentioned by many researches in water making, one of them is the use of color palette and color index which is also know as ordering and mapping color method. In this method, the substitute color found through all colors in the pallets so this process gives the longer time in bit watermark inserting process. In this paper, ordering and mapping color which use color pallet of an image will be modified to increase the speed of the process by using eight neighborhoods approximation. From experimental result conducted to 30 images, it can be concluded that the proposed approximation has taken the shorter time than the conventional method.